Accountability of Partnership Program Funds in State-Owned Enterprises - Aryzona, Ayu Putrisia; Alfatih, Andy; Effendi, Sofyan (Open Access Indonesia Journal of Social Sciences, 2018)
ABSTRACT This research was motivated by a problem regarding the late payment of bad debts that are not in accordance with the contract of PT Semen Baturaja (Persero), one of State Owned Enterprises, and the limitation of bad debt which has not been maximally carried out. This study aims to look at the accountability of partnership program funds at PT Semen Baturaja (Persero). This research uses descriptive qualitative method. Data collection techniques used in this study were in-depth interviews, observation, and documentation. The results of this study indicate that the accountability of partnership program funds is not good because there are still incomplete and irrelevant financial statement information and there are still fostered partners who do not carry out obligations, receipt of funds that are not in accordance with the specified characteristics and limitation of receivables only once although the number of receivables is increasing.